DNA barcoding of marine ornamental fishes from India. (2nd September 2016) - Bamaniya, Dhaval C.; Pavan-Kumar, A.; Gireesh-Babu, P.; Sharma, Niti; Reang, Dhalongsaih; Krishna, Gopal; Lakra, W. S.
Abstract: India has rich marine ornamental fish diversity with 400 fish species distributed in Gulf of Munnar/Palk Bay, Gulf of Kutch, and in reefs around Andaman & Nicobar and Lakshadweep Islands. Marine ornamental fish identification at the field level is very difficult because of their high diversity and profound changes in appearance during their developmental stages and camouflage. To facilitate ornamental fish trading with ease and in compliance with the biodiversity act, DNA barcoding technique could be used to accurately identify species. In this study, DNA barcodes were generated for 31 species of commercially important marine ornamental fishes from India. The average genetic distance (K2P model) within species, genus, and family was 0.446, 13.08, and 20.09%, respectively. Intraspecific variation has increased several folds (15–20 times) after including conspecific sequences from different geographical locations. The presence of allopatric lineages/cryptic species was observed in the Indo-pacific region. The NJ tree constructed based on K2P values showed distinct clusters shared by congeneric species specific to populations.